Novel Lipid-Based Carriers of Provitamin D3: Synthesis and Spectroscopic Characterization of Acylglycerol Conjugated with 7-Dehydrocholesterol Residue and Its Glycerophospholipid Analogue - Witold Gładkowski; Susanna Ortlieb; Natalia Niezgoda; Anna Chojnacka; Paulina Fortuna; Paweł Wiercik (Molecules)
The aim of this research was to design and synthesize new lipid conjugates of 7-DHC that could serve as a new storage form of esterified provitamin D3, increasing the reservoir of this biomolecule in the epidermis and enabling controlled production of vitamin D3 even during periods of sunlight deficiency. Acylglycerol and glycerophospholipid containing succinate-linked provitamin D3 at the sn-2 position of the glycerol backbone were synthesized from dihydroxyacetone (DHA) and sn-glycerophosphocholine (GPC), respectively. The three-step synthesis of 1,3-dipalmitoyl-2-(7-dehydrocholesterylsuccinoyl)glycerol involved the esterification of DHA with palmitic acid, reduction of the carbonyl group, and conjugation of the resulting 1,3-dipalmitoylglycerol with 7-dehydrocholesterol hemisuccinate (7-DHC HS). The use of NaBH3CN as a reducing agent was crucial to avoid acyl migration and achieve the final product with 100% regioisomeric purity. For the preparation of 1-palmitoyl-2-(7-dehydrocholesterylsuccinoyl)-sn-glycero-3-phosphocholine, a two-step process was applied, involving the esterification of GPC at the sn-1 position with palmitic acid, followed by the conjugation of 1-palmitoyl-sn-glycero-3-phosphocholine with 7-DHC HS. Alongside the main product, a small amount of its regioisomer with provitamin D3 linked at the sn-1 position and palmitic acid at the sn-2 position was detected, indicating acyl migration from the sn-1 to the sn-2 position in the intermediate 1-palmitoyl-sn-glycerophosphocholine. The synthesized novel lipids were fully characterized using spectroscopic methods. They can find applications as novel lipid-based prodrugs as additives to sunscreen creams.